Daya Tarik Wisata Unggulan Di Daerah Transit Kota Pematangsiantar, Sumatera Utara - Situmorang, Christiani; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2018)
Research on the travel attractions featured in transit area Pematangsiantar, North Sumatra, intend to find an activity that is do by tourist in transit and to know the attraction featured of travel attraction for transit tourist. Data collection techniques in this study, by observation, in-depth interviews with the actors of tourism in Pematangsiantar, and literature study by means of documentation using a variety of documents, such as books and literature. Documentation can also be done by taking a picture in Pematangsiantar. The data obtained were analyzed by using qualitative descriptive analysis of the data that describes, depicts, and systematic explanation of the data obtained in the field with the aim of obtaining a clear and objective. This research is located in Pematangsiantar, North Sumatra. The results of this research is to be able to make Pematangsiantar as transit areas must be identified ahead of the tourist attraction featured for transit travelers. To determine the leading tourist appeal, it is necessary to know the behavior patterns of travelers in transit while in Pematangsiantar, starting from what place you visit, what you buy, and how long the stay. Of traveler behavior patterns, it can be concluded that the appeal is the leading tourist tourist attraction most visited by tourists in transit and has many tourist activities, are: culinary tourism, cultural tourism, nature tourism and religious tourism.   Keywords : Tourist Attraction Featured, Transit Area